Deed of Settlement as A Dispute Object based on HIR and Supreme Court Regulation No. 1/2016 - Hazar Kusmayanti; Lucky Dharmawan (Universitas Ahmad Dahlan, 2020)
Introduction to The Problem: It is uncommon for a case that has been decided by a judge and has the legal force to be retained and then brought back to Court by one party for a lawsuit. This kind of case contradicts the principles and applicable law, such as the case that the researcher found in Case No. 22/Pdt.G/2016/PN. Sal.Purpose/Objective Study: This paper intends to discuss the legal problem of the re-submission of the deed of settlement as the object of a breach.Design/Methodology/Approach: This research is doctrinal legal research. The data are secondary data which analyzed qualitatively. Following the approach method used, the study is conducted on norms and principles contained in secondary data, from the primary, secondary, and tertiary legal materialsFindings: The results of the study show that, first, deed of settlement cannot be an object of default because it has been inkracht. Secondly, Salatiga court judges did not consider the principle of ne bis in idem under Article 10 (1) The Judicial Power Act. The president of judges shall be able to carry out the role or power under Article 119 of the HIR, which is to provide advice to those who wish to file a lawsuit.Paper Type: Research Article.